2019
DOI: 10.1038/s41437-019-0192-4
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-by-environment interaction of fertility traits in Danish Holstein cattle using a single-step genomic reaction norm model

Abstract: Genotype-by-environment (G × E) interactions could play an important role in cattle populations, and it should be considered in breeding programmes to select the best sires for different environments. The objectives of this study were to study G × E interactions for female fertility traits in the Danish Holstein dairy cattle population using a reaction norm model (RNM), and to detect the particular genomic regions contributing to the performance of these traits and the G × E interactions. In total 4534 bulls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
44
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 47 publications
11
44
0
3
Order By: Relevance
“…The variance components estimated using reaction norm models with A and H matrices were very similar. This result is consistent with previous reports on pigs (Silva et al., 2014), cattle (Oliveira et al., 2018) and Danish Holstein cattle (Zhang et al., 2019). However, regardless of the existence of G × E interactions, higher prediction accuracies were observed in models based on H matrix compared to A matrix, for both reaction norm models and reduced models.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The variance components estimated using reaction norm models with A and H matrices were very similar. This result is consistent with previous reports on pigs (Silva et al., 2014), cattle (Oliveira et al., 2018) and Danish Holstein cattle (Zhang et al., 2019). However, regardless of the existence of G × E interactions, higher prediction accuracies were observed in models based on H matrix compared to A matrix, for both reaction norm models and reduced models.…”
Section: Discussionsupporting
confidence: 94%
“…For the amount of variance of the slope (σa12) in relation to variance of the intercept (σa02), σa12/σa02 were 0.002 and 0.348 based on H matrix for AGE and BFT, respectively. Low correlation between the intercept and slope as well as large σa12 could potentially mean the re‐ranking of animals across different environments, which means that the best genotype (phenotype) in one environment may not be the best in another environment (Oliveira et al., 2018; Santana, Eler, Cardoso, Albuquerque, & Ferraz, 2013; Su et al., 2006; Zhang et al., 2019), high correlation between intercept and slope as well as small variance of slope indicate small or no G × E interactions for AGE. In addition, the effects estimated for the 10 top SNPs based on the p ‐values of the slopes were plotted against the EV (Figure 7), which also showed that there were no changes in the effects of the SNPs across EVs for AGE.…”
Section: Discussionmentioning
confidence: 99%
“…G × E interactions play an important role in pig populations, and they should be considered in breeding programs to select the best animals in different environments [ 11 , 24 ]. The detection of G × E interactions relies on a genetic correlation of 0.8 for one trait in different environments, the threshold suggested by Robertson [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differential animal responses across environmental conditions have been assessed through reaction norm models (RNM), describing animal sensitivity to environmental changes (Calus & Veerkamp 2003;Kolmodin et al 2003). Genomic information has been used to assess G9E interactions, representing a promising alternative to evaluating traits strongly influenced by environmental factors (Lillehammer et al 2008(Lillehammer et al , 2009Silva et al 2014;Mota et al 2016;Zhang et al 2019). According to Hayes et al (2016), the inclusion of genomic information in RNM has the potential to overcome the low quantity of phenotypic information from sires with offspring in a wide range of environments, given that the genotyped animals are well distributed across different environments.…”
Section: Introductionmentioning
confidence: 99%